(untitled) (INNOVATIVE ECONOMY, 2026)
Anhelko I.V. BASIC PRINCIPLES AND MECHANISMS OF STATE REGULATION OF ENTREPRENEURSHIP UNDER CONDITIONS OF UNCERTAINTY AND STRUCTURAL CHANGE Purpose. The aim of the article is to highlight the main principles and mechanisms of state regulation of entrepreneurship under conditions of uncertainty and structural changes, to analyse their effectiveness, and to identify key directions for improvement to ensure the sustainable development of the entrepreneurial sector and enhance its adaptability to economic challenges. Methodology of research. To achieve the stated objective, both general scientific and specialized research methods were used. In particular, methods of analysis and synthesis were applied to outline the theoretical content of state regulation of entrepreneurship; the generalization method was used to identify principles, methods, instruments, and organizational forms of state influence on entrepreneurial activity; the method of structural and functional analysis was employed to reveal the interrelations between elements of the state regulation mechanism and determine their role in ensuring the resilience of the entrepreneurial sector; and a systems approach was applied to consider state regulation as an integrated system under conditions of uncertainty and structural changes. Findings. The study established that state regulation of entrepreneurship under conditions of uncertainty and structural changes must be systemic and adaptive. It was determined that its main principles are implemented through a set of guidelines that ensure the rationale and consistency of state influence with public interests. It was substantiated that the implementation of these principles occurs through the mechanism of state regulation of entrepreneurship, which serves as a practical instrument of state policy. The main components of this mechanism – methods, instruments, and organizational forms of regulatory activity – were characterized. It was established that methods of state influence acquire practical content through appropriate instruments, which ensure the achievement of strategic regulatory objectives. It was determined that under conditions of structural transformations, the role of financial incentives, digitalization of regulatory procedures, institutional support for small and medium-sized enterprises, and the development of innovative activities increases. It was established that improving the effectiveness of state regulation is possible by ensuring transparency of regulatory procedures, coordination of actions among authorities, and orientation towards long-term economic stability. Directions for improving the mechanism of state regulation of entrepreneurship were substantiated, including enhancing the flexibility of regulatory policy, strengthening institutional capacity, and creating a favourable environment for the development of entrepreneurial activity. Originality. The theoretical approach to state regulation of entrepreneurship has been improved through the systematization of methods, instruments, and organizational forms of government intervention, which, unlike existing approaches, makes it possible to comprehensively assess the effectiveness of the mechanism for supporting the entrepreneurial sector under conditions of economic instability. Further development has been given to the substantiation of directions for improving state regulation of entrepreneurship through the integration of regulatory procedure digitalization, institutional support for small and medium-sized enterprises, financial incentives, and innovation support measures, which contributes to enhancing the adaptability and resilience of business entities to contemporary economic challenges. Practical value. The research results can be used by government authorities to improve the effectiveness of regulatory measures, create a predictable and stable environment for the entrepreneurial sector, stimulate innovative activity, and promote the development of small and medium-sized enterprises. Key words: state regulation, entrepreneurship support mechanism, regulatory methods, instruments of state influence, organizational forms, adaptability, economic stability.